PROBLEMS IN SUSTAINABLE DEVELOPMENT OF RURAL TOURISM IN UZBEKISTAN (Scientific Journal of Actuarial Finance and Accounting, 2024)
This article explores the challenges faced in the sustainable development of rural tourism in Uzbekistan. Despite the country's rich cultural heritage and diverse landscapes, various obstacles hinder the progress of rural tourism. This study identifies key issues such as infrastructure deficits, lack of skilled workforce, environmental concerns, and inadequate policy support. Through a mixed-methods approach, combining qualitative interviews and quantitative data analysis, the research provides insights into the current state of rural tourism and suggests strategic solutions for sustainable growth.